KINERJA KARYAWAN: PERAN MOTIVASI KERJA, KEPUASAN KERJA DAN FLEKSIBILITAS KERJA : STUDI KASUS DRIVER GRAB DI JAKARTA TIMUR - Megawati Sihite; Didin Hikmah Perkasa; Magito Magito; Lingga Yuliana; Agung Surya Dwianto (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the effect of work motivation, job satisfaction and work flexibility on the performance of grab drivers in East Jakarta. This research is descriptive quantitative. The population used in this study were 100 Grab drivers in Cilangkap, East Jakarta. Sampling of 100 people using saturated samples. Data collection tools using questionnaires that have been tested for validity and reliability are distributed via google form. Data analysis was carried out using SEM PLS(Partial Least Square) through testing the outer model, inner model and hypothesis testing. The initial stage determines the indicators of each variable. The next stage tests the validity and reliability of each indicator. The results of his research prove that work motivation, job satisfaction, and work flexibility affect performance. The adjusted R square value shows that 75.7% of driver performance is influenced by the independent variables, namely Work Motivation, Job Satisfaction and Work Flexibility